ANALISIS PENGARUH BELANJA BANTUAN SOSIAL, PENDIDIKAN DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN PENDUDUK DI PROVINSI RIAU - Vinny Alvionita Riva; Sri Endang Kornita; Yusni Maulida (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
This study aims to analyze the effect of spending on social assistance, education and economic growth on poverty levels in Riau Province. This study uses secondary data obtained from the Central Statistics Agency (BPS) of Riau Province in 2007 - 2019, while the data analysis technique is to use the multiple linear regression method. The results of the study found that spending on social assistance had no significant effect on poverty levels in Riau Province, meaning that changes in social assistance in Riau Province had not been able to encourage change for the poor. Education has a significant effect on poverty levels in Riau Province, which means that any increase in education seen from the average length of schooling will encourage a decline in the poor. Economic growth has no significant effect on poverty levels in Riau Province, meaning changes in economic growth in Riau Province.